Interventions for Keeping Adolescent Girls in School in Low- and Middle-Income Countries: A Scoping Review - Sampa, Mutale; Musukuma, Mwiche; Fisa, Ronald; Musonda, Patrick; Young, Taryn (Frontiers in Education, 2021)
Background: Adolescent girls dropping out of school may lead to gender inequality, high illiteracy levels, single motherhood, unemployment and many more undesirable outcomes that inhabit human capital development for girls. It is therefore important to put measures in place to support adolescent girls to stay in school. The objectives of the scoping review were to identify and describe the types of studies conducted to assess interventions for keeping adolescent girls in school and to describe these interventions in low and middle-income countries. Methods and results: A comprehensive search was done in Epistemonikos, Social Science Citation index, Embase, OVID Medline, the Campbell Collaboration Library and CENTRAL in March 2020. The search yielded 3295 studies of which 18 studies were eligible for inclusion. All the 18. The included studies included studies were primary studies and 12 out of these were a Randomized Controlled studiesy design. The other study designs of included studies were mixed methods longitudinal design, random evaluation, cross section e.tc. The interventions in the included studies were categorized as follows; provision of funding, school-based interventions for leaners, community-based interventions and education systems intervention. Provision of school fees, and other school supplies have shown evidence of reducing school dropouts, increasing enrolments and school attendance while interventions like hygiene promotion and water treatment in a study done in Kenya found no significant evidence to support the observed effect on school attendance. Conclusions: The scoping review found that several primary studies have been done on interventions to keep adolescent girls in school. However, there is need for more research to be done. Therefore, the authors propose to conduct a systematic review on the effect of provision of sanitary towels to adolescent girls on school retention in low and middle income countries.